Klinik Ng Poh Huat / Beinah Karim, Nurul Shahida Baharum … [et al.] - Karim, Beinah; Baharum, Nurul Shahida; Mohd Ismail, Ros Laili; Yahya, Siti Katijah (2019)
Klinik Ng Poh Huat is a general medical practice which was established in September 2013 by Dr. Ng Poh Huat as its owner and also a general practitioner. This clinic is located in Bandar Mahkota Cheras and opens to the customers daily starting from 9a.m. until 9 pm.. The owner also serves as a consultant physician, performs medical examinations, general illness, and minor procedures in this clinic. He is assisted by four Clinical Assistants which continues further in becoming the backbone of the clinic to ensure it is operating well.